2018
DOI: 10.1101/344093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opening Pandora’s box: high level resistance to antibiotics of last resort in Gram negative bacteria from Nigeria

Abstract: 23Antimicrobial resistance (AMR) is a global problem but information about the 24 prevalence and mechanisms of resistance in sub-Saharan Africa are lacking. We 25 determined the percentage of drug resistant isolates and resistance mechanisms in 307 26Gram negative isolates randomly collected from south western Nigeria. Susceptibility 27 testing revealed 78.1%, 92.2% and 52.6% of all isolates were resistant to 28 fluoroquinolones, third generation cephalosporins and carbapenems respectively. There 29 were more … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Two ST90 isolates are identical, differ from a third by only 11 SNPs, and likely represent an outbreak. Our findings add to information that is chronicling ExPEC lineages of importance within Nigeria [1416, 52, 53], other parts of Africa [16, 54], and other low-middle-income countries [16, 55].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Two ST90 isolates are identical, differ from a third by only 11 SNPs, and likely represent an outbreak. Our findings add to information that is chronicling ExPEC lineages of importance within Nigeria [1416, 52, 53], other parts of Africa [16, 54], and other low-middle-income countries [16, 55].…”
Section: Discussionsupporting
confidence: 66%
“…Although studies conducted in Africa and other low-and middle-income countries (LMICs) have shown the abundance of invasive E. coli [9,10], these studies are too few and far between so that ExPEC and AMR epidemiology are poorly understood [7,11]. In Nigeria, there is sparse molecular information on ExPEC, but a few studies point to likely clonal expansion of resistant lineages and local presence of pandemic clones of concern [12][13][14][15][16]. These studies provide valuable information but represent an insufficient picture of ExPEC clones in Nigeria with few data available from South.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies conducted in Africa and other low-and middle-income countries (LMICs) have shown the abundance of E. coli in infections from normally sterile sites [9,10], these studies are few and far between, so that ExPEC and their AMR epidemiology are poorly understood [7,11]. In Nigeria, there is sparse molecular information on ExPEC, but a few studies point to likely clonal expansion of resistant lineages and local presence of pandemic clones of concern [12][13][14][15][16]. These studies provide valuable information but represent an insufficient picture of ExPEC clones in Nigeria, with little data available from the South.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, carbapenem-resistance rates are revealed as 0.1% and 5.3% for E. coli and Klebsiella pneumoniae (K. pneumoniae), correspondingly, whereas in Europe, most nations report resistance rates below 1% for both pathogens. 19 Even though studies from Africa stated a carbapenem resistance of (3.8-52.6%), [20][21][22][23] still there are a few data on CR-GNB in Africa. 21 While there are a few studies in Ethiopia conveyed on CR with a range of 2-27.1%, [24][25][26][27] however, there is limited data in the study area.…”
Section: Introductionmentioning
confidence: 99%